Cultural adaptation and psychometric validation of the Health Literacy Instrument for Adults with Tuberculosis (HELIA-TB) in India - Arohi Chauhan; Kapil Govani; Jaya Singh Kshatri; Sandeep Chauhan; Punit Patel; Joseph Baluku; Abhinav Sinha; Marjan Van Den Akker; Jesse Jansen; Jose Valderas; Sanghamitra Pati (PLoS ONE, 2026)
Background Tuberculosis (TB) remains a critical public health challenge in India, where sustained patient engagement is essential for its effective management. Despite the pivotal role of health literacy, the ability to access, understand, appraise, and apply health-related information in treatment adherence and outcomes, few tools are TB specific, culturally attuned to India, and psychometrically validated. The Health Literacy Instrument for Adults (HELIA), developed in Iran, is a multidimensional, World Health Organization (WHO)-aligned measure with proven reliability and open access, making it an ideal candidate for adaptation. This study aimed to culturally adapt and validate the HELIA for use among adults receiving TB treatment in India (HELIA-TB). Methods An exploratory sequential mixed-methods design was employed for the cultural adaptation and psychometric validation of the HELIA-TB in Junagadh district, Gujarat, India, between March 2024 and March 2025. The qualitative phase included expert review, forward translation, cognitive interviews with adults with TB and  frontline healthcare workers, back translation, and pilot testing, following international cross-cultural validation guidelines. Findings from the qualitative phase directly informed item modification, simplification of terminology, and contextual adaptation of the HELIA-TB prior to quantitative psychometric validation. The finalized instrument was subsequently administered to 393 adults with TB to assess internal consistency, test-retest reliability, content validity, and construct validity. Results HELIA-TB retained the original five domains, access, reading, understanding, appraisal, decision-making with TB specific modifications. Internal consistency and test-retest reliability were high (α = 0.82–0.89 across domains; 0.86 overall; ICC = 0.88), and so was content validity (S-CVI/Ave = 0.92). Health literacy scores were significantly associated with treatment adherence (Cohen's d = 0.89, p < 0.001) and self-rated health (Cohen's d = 0.76, p < 0.001). No significant differences were observed by TB type or drug resistance status. Conclusions The adapted HELIA-TB demonstrated satisfactory psychometric properties and may support assessment of health literacy and development of targeted TB care interventions in the Indian context.